Stop the Presses? Moving From Strategic Silence to Strategic Amplification in a Networked Media Ecosystem. (February 2021) - Donovan, Joan; boyd, danah
In a media ecosystem besieged with misinformation and polarizing rhetoric, what the news media chooses not to cover can be as significant as what they do cover. In this article, we examine the historical production of silence in journalism to better understand the role amplification plays in the editorial and content moderation practices of current news media and social media platforms. Through the lens of strategic silence (i.e., the use of editorial discretion for the public good), we examine two U.S.-based case studies where media coverage produces public harms if not handled strategically: White violence and suicide. We analyze the history of journalistic choices to illustrate how professional and ethical codes for best practices played a key role in producing a more responsible field of journalism. As news media turned to online distribution, much has changed for better and worse. Platform companies now curate news media alongside user generated content; these corporations are largely responsible for content moderation on an enormous scale. The transformation of gatekeepers has led an evolution in disinformation and misinformation, where the creation and distribution of false and hateful content, as well as the mistrust of social institutions, have become significant public issues. Yet it is not just the lack of editorial standards and ethical codes within and across platforms that pose a challenge for stabilizing media ecosystems; the manipulation of search engines and recommendation algorithms also compromises the ability for lay publics to ascertain the veracity of claims to truth. Drawing on the history of strategic silence, we argue for a new editorial approach—"strategic amplification"—which requires both news media organizations and platform companies to develop and employ best practices for ensuring responsibility and accountability when producing news content and the algorithmic systems that help spread it.